Descemet Membrane Suturing for Large Descemet Membrane Detachment After Cataract Surgery. Issue 1 (January 2020) - Das, Manoranjan; Begum Shaik, Muneera; Radhakrishnan, Naveen; Prajna, Venkatesh N.
Abstract : Purpose: To study the outcomes of Descemet membrane (DM) suturing for moderate to severe Descemet membrane detachment (DMD) after cataract surgery. Methods: This is a retrospective case review of all patients who underwent DM suturing for moderate to severe DMD after cataract surgery in a tertiary training eye care hospital from January 2017 to December 2017. Demographic details, type of cataract, type of cataract surgery, intraoperative complications, severity of DMD, time to repair, and post-DM suturing visual and clinical outcomes were documented. Results: Forty-nine patients were included during the study period with a mean age of 67.7 ± 9.7 years. In total, 79.5% had immature cataracts. Median precataract LogMAR visual acuity was 0.78 (IQR 0.69–1.13). In total, 61.2% underwent manual small-incision cataract surgery, 32.6% had phacoemulsification, 2% had extracapsular cataract extraction (ECCE), and 6% underwent small-incision cataract surgery with trabeculectomy. In total, 44.9% were operated on by trainees and 55.1% were operated on by consultants. In total, 22.4% had primary air descemetopexy during the cataract surgery and failed treatment. All patients had attached DM in the immediate postoperative period. None of them had secondary angle closure glaucoma. At the final follow-up, 42 (85.7%) had clear corneas and 7 (14.3%) had corneal decompensation needing endothelial keratoplasty. Of these 7 patients, 2 (28.5%) had Fuchs dystrophy and 3 (42.8%) had associated DM loss. The median LogMAR visual acuity at the final follow-up was 0.39 (IQR 0.3–0.78). Conclusions: DM suturing can reattach DM, especially in moderate to severe, recurrent DMD with fewer postoperative complications and thereby reduce the need for corneal transplantation.